Deliberating Marriage Payment through Jujuran within Banjarese Community - Hafidzi, Anwar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2020)
Abstract: In the Banjarese culture of marriage, besides dowry, jujuran is also paid by the man to the woman in a certain amount of money under the request of the women’s family. Many researchers have discussed dowry, but only a few have revealed the reality of jujuran as a sign of marriage. This study was conducted with a phenomenological approach as part of a qualitative approach. The study aims to understand and describe a phenomenon about the subjects’ experiences regarding the Banjar community's marriage system, South Kalimantan, Indonesia. The research argued that the Banjarese use jujuran as a sign of a marriage agreement. It also asserts that although jujuran aims to improve their children's economic standard when married, it reveals that this system determines who has the right to propose to their daughters. The paper also maintains that the local practice of jujuran payment has, to some extent, violated the rights of the women to their choice in marriage, mainly when the prospective grooms are unable to pay the jujuran. Abstrak: Dalam budaya perkawinan Banjar, selain mas kawin, jujuran juga dibayarkan oleh laki-laki kepada perempuan dalam jumlah tertentu atas permintaan keluarga perempuan. Banyak peneliti telah membahas tentang mahar, namun hanya sedikit yang mengungkap realitas jujuran sebagai tanda pernikahan. Penelitian ini dilakukan dengan pendekatan fenomenologi sebagai bagian dari pendekatan kualitatif. Penelitian ini bertujuan untuk memahami dan mendeskripsikan fenomena sistem perkawinan di masyarakat Banjar, Kalimantan Selatan, Indonesia. Hasil penelitian menunjukkan bahwa orang Banjar menggunakan jujuran sebagai tanda akad nikah. Hal ini juga menegaskan bahwa meski tujuan jujuran adalah untuk meningkatkan taraf ekonomi anak-anak mereka ketika mereka menikah, tetapi sistem ini dapat menentukan siapa yang berhak melamar anak perempuannya. Penelitian ini juga menyatakan bahwa praktik pembayaran jujuran setempat sampai batas tertentu telah melanggar hak perempuan atas pilihan mereka dalam pernikahan, terutama ketika calon pengantin pria tidak mampu membayar jujuran.